Pyogenic granuloma of the upper lip: A common lesion in an uncommon location - Pratibha Poudel, MDS; Nitesh Chaurasia, MDS; Vinay Marla, PhD; Ritesh Srii, MDS (Journal of Taibah University Medical Sciences, 2019)
Pyogenic granuloma is a non-neoplastic reactive lesion that commonly occurs in gingiva. It is rarely found in other locations such as the lips, tongue, palate and buccal mucosa. Lesions affecting the upper lip are even rarer and very few cases have been reported in the literature. In such situations, the lesion may mimic other conditions such as minor salivary gland tumours, mesenchymal tumours, and infectious lesions, which may create diagnostic difficulty. This case report describes an uncommon location of pyogenic granuloma occurring on the upper lip in a 49-year-old male patient. Keywords: Gingival lesions, Granuloma, Pyogenic, Upper lip